Analysis of Factors Influencing Emotional Dependence of Early Childhood Children in the Gajahwong School Community, Yogyakarta - Sriyanti Nihi; Riana Mashar; Khamim Zarkasih Putro; Dwi Hastuti (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study aims to analyze the factors influencing emotional dependence in early childhood within the Gajahwong School Community in Yogyakarta. A qualitative design was employed, involving four children aged 3–4 years as subjects and parents and teachers as informants. Participants were selected using purposive sampling. Data were collected through observation and in-depth interviews, then analyzed thematically by identifying, categorizing, and interpreting emerging patterns, and presented in narrative form supported by previous research.The study's results indicate that children's emotional dependence is influenced by two primary factors: family and socioeconomic circumstances, and psychological factors. Family factors include insecure attachment patterns, insufficiently emotionally responsive parenting, and parents' limited understanding of how to regulate their children's emotions under socioeconomic stress. Empirical findings indicate that children may exhibit behaviors such as prolonged crying when separated from their parents, difficulty adapting in the classroom, a tendency to cling to teachers as substitute attachment figures, and spontaneous emotional reactions when facing problems with peers.In addition, children's psychological profiles are marked by excessive separation anxiety and a limited capacity for independent self-regulation. The intensity and manifestation of these behaviors vary among children, indicating that emotional dependence is not a fixed condition but is shaped by dynamic interactions between family relational experiences and the child's psychological state. Based on these findings, collaborative, context-sensitive interventions are needed, such as parenting education programs attuned to families' socioeconomic circumstances, emotion-regulation training for parents and educators, and adjustments to the school environment to better support children's transitions and emotional adaptation.